PENGGUNAAN TARGET COSTING DALAM PENGEMBANGAN PRODUK - PUTRI ZANUFA SARI (Universitas Katolik Widya Mandala Surabaya, 2012)
Tight competition caused the company should try to make adjustments to the consumer. Strict competition makes consumers have many choices of products for consumption. Companies should pay attention to the issue price if you want to be the choice of consumers in purchasing decisions.Target costing seems to fit the needs of the company's price adjustment related problems at more stringent levels of competition. Target costing is an attempt to set the cost of the product in accordance with the selling price to be determined. Target costing is the selling price minus the expected profit rate. The use of target costing will cause the company is able to sell products at a price that is acceptable to consumers. Condition of existing opportunities for successful product development. The use of target costing works well, if supported by the ability to create efficiencies and cost effectiveness in the production process. It is intended that each production activity is able to bring operational costs down, and eventually be able to produce cost calculations in accordance with the target. It is also capable of producing products with low price in accordance with the quality expectations of consumers but are still acceptable.